Local anaesthetics: Theoretical aspects. Issue 4 (April 2022) - Allen, Gareth; Butler, Rebecca
Local anaesthetics are frequently used in both primary and secondary care. These agents transiently reduce the nervous conduction of nociceptive signals, reducing sensations of pain. In primary care, local anaesthetics are often used for minor surgical procedures. However, there are other uses for these agents. It is important to understand the issues encountered when using local anaesthetics in primary care. This review will cover clinical use, relevant pharmacology and adverse effects of the different local anaesthetic preparations.